Inspiratory Muscle Training Intensity in Patients Living with Cardiovascular Diseases: A Systematic Review - Anaïs Beaujolin; Jessica Mané; Céline Presse; Jordana Barbosa-Silva; Michela Bernini; Camilo Corbellini; Raphael Martins de Abreu (Hearts, 2024)
The benefits of inspiratory muscle training (IMT) have been demonstrated in patients with cardiovascular diseases (CVD); however, the optimal training intensity is not yet fully clarified. The purpose of this study was to review the impact of IMT intensity on respiratory muscle strength, functional and exercise capacity, pulmonary function, and quality of life in patients with CVD. This systematic review was carried out according to PRISMA statement and registered in the PROSPERO database (review protocol: CRD42023442378). Randomized controlled trials were retrieved on 3 July 2023 in the following electronic databases: Web of Science, PubMed, EMBASE, and SCOPUS. Studies were included if they assessed the impact of isolated IMT on CVD patients in comparison with sham, different intensities and/or intervention groups. Eight studies were included for final analysis; IMT consistently led to significantly greater improvements in inspiratory muscle strength compared to control (CON) groups. The intensity of IMT varied in the studies based on different percentages of maximal inspiratory pressure (MIP), ranging from 25% to 60% of MIP. The time of intervention ranged from 4 to 12 weeks. Despite this variability, the studies collectively suggested that IMT is beneficial for enhancing CVD patients’ conditions. However, the optimal intensity range for benefits appeared to vary, and no single intensity emerged as universally superior across all studies.